A study on the relationship between organizational climate and job satisfaction among primary school teachers at Bukit Jelutong / Mohd Rohaizi Seman @ Ab Rahman - Seman @ Ab Rahman, Rohaizi (2014)
The purpose of this study was to examine the influence of perceived job satisfaction and organizational climate. It was also to examine the relationship between both variables. 107 daily primary school teachers in SK Bukit Jelutong completed the surveys for this study. They were selected based on simple random sampling. Data were collected using the survey method and were analysed using both descriptive and correlational statistics. Based on the data collected, the findings showed that generally the daily primary school teachers in SK Bukit Jelutong have a moderate level of job satisfaction. They also have moderate level perceptions towards their organizational climate. The findings also revealed that there was a low positive relationship between job satisfaction and organizational climate. From finding of the study, it could be summarized that organizational climate plays a significant role in the teachers of the primary school job satisfaction. In addition, it was also indicated from the study that reward and remuneration plays an important role in providing the level of job satisfaction among the educational staffs of the school. Further study was recommended by broadening the size of the respondents to view their perceptions of job satisfaction in relation to their organizational climate.